Friction and wear behaviour of bacterial cellulose against articular cartilage - Lopes, J. L. (2011)
Bacterial cellulose (BC) is a natural and biocompatible material with unique properties, such as high water holding capacity, ultra-fine fibre network and high strength that makes it an attractive material for the repair of articular cartilage lesions. However, data on the tribological properties of BC is very scarce, particularly if natural articular cartilage is involved in the contact. In this work, unmodified BC pellicles were grown from Gluconacetobacter xylinus in order to be used as tribological samples against bovine articular cartilage (BAC) in the presence of phosphate buffered saline (PBS). The tribological assessment of the sliding pairs was accomplished using reciprocating pin-on-flat tests at 37ºC. The reciprocating sliding frequency and stroke length were kept constant at 1 Hz and 8 mm, respectively. Contact pressures ranging from 0.80 to 2.40 MPa were applied. The friction coefficient evolution was continuously monitored during the tests and the release of total carbohydrates into the lubricating solution was followed by means of the phenol-H2SO4 method as an attempt to evaluate wear losses. The morphology of worn surfaces was characterized by SEM/EDS and the main wear mechanisms were identified. Low friction coefficient values (~ 0.05) combined with the preservation of the mating surfaces (BC and BAC) indicate the potential of BC to be used as artificial cartilage for articular joints.